Correlation of Knowledge, Attitudes, and Actions of Coffee Farmers in Implementing Good Agriculture Practice (GAP) in Solok District - Putri, Afrianingsih; Rahmat, Syahni; Hasnah, Hasnah; Miko, Alfan (JSEP (Journal of Social and Agricultural Economics), 2023)
Implementation of Good Agriculture Practice (GAP) in coffee farming as an effort to increase productivity. However, many farmers do not apply good cultivation techniques in their farming activities. research aims to analyze the relationship between knowledge, attitudes, and actions of farmers in implementing GAP. The method used was a survey and sampling technique using non-probability sampling (saturated sampling) of 120 Arabica coffee farmers in Lembah Gumanti and Pantai Cermin Districts, Solok Regency. Data were analyzed quantitatively using descriptive statistics from the results of frequency distribution tables and correlation analysis using Spearman Rank correlation test calculations. The analysis results show that farmers' knowledge of implementing GAP is high, and farmers' attitudes are quite good, while farmers' actions in implementing GAP are in the inappropriate category. Correlation analysis shows a significant relationship (significance 0.05) between knowledge, attitudes, and attitudes towards farmer actions (p= 0.00). There is no significant relationship between knowledge and action (p=0.974). In implementing GAP, farmers need to be given continuous counseling so that their attitudes and knowledge improve and farmers have high motivation to implement GAP.